Sensitivity and specificity of the circulating cathodic antigen rapid urine test in the diagnosis of Schistosomiasis mansoni infection and evaluation of morbidity in a low- endemic area in Brazil - Fernanda Teixeira Ferreira; Thiago André Fidelis; Thiago Almeida Pereira; Alba Otoni; Leonardo Campos Queiroz; Frederico Figueiredo Amâncio; Carlos Maurício Antunes; José Roberto Lambertucci (Revista da Sociedade Brasileira de Medicina Tropical)
Abstract INTRODUCTION: The Kato-Katz technique is the standard diagnostic test for Schistosoma mansoni infection in rural areas. However, the utility of this method is severely limited by the day-to-day variability in host egg excretion in the stool. In high-transmission areas, the point-of-care circulating cathodic antigen (POC-CCA) urine assay has proven to be a reliable test. However, investigations of the reliability of the POC-CCA assay in low-transmission regions are under way. This study aimed to evaluate the sensitivity and specificity of the POC-CCA assay and the morbidity of schistosomiasis in a low-endemic area in Brazil. METHODS: Pains City is a low-transmission zone for schistosomiasis. A total of 300 subjects aged 7-76 years were randomly selected for the POC-CCA cassette test. For S. mansoni diagnosis, three stool samples on six slides were compared with one urine sample for each subject. The sensitivity and specificity in the absence of a gold standard were calculated using latent class analysis. Clinical examinations and abdominal ultrasounds were performed in 181 volunteers to evaluate morbidity associated with schistosomiasis. RESULTS: The sensitivity and specificity of the Kato-Katz technique were 25.6% and 94.6%, respectively. By contrast, the sensitivity and specificity of the POC-CCA assay were 68.1% and 72.8%, respectively. Hepatosplenic schistosomiasis was diagnosed in two patients (1.1%). CONCLUSIONS: Overall, the POC-CCA urine assay proved to be a useful test for diagnosing S. mansoni in a low-endemic area in Brazil. Severe clinical forms of schistosomiasis can be present even in such low-endemic areas.